2019
DOI: 10.3390/met9121277
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and Mechanistic Understanding of New TF400 Titanium Alloy

Abstract: The isothermal hot compression behavior of new Ti–Fe–B (named as TF400) alloy was investigated in the temperature range of 750–950 °C and strain rate range from 0.01 to 10 s−1 with the maximum height reduction of 60% by using a Gleeble 3800 thermal simulator. By considering the effect of strain via variable material parameters, a modified constitutive model was proposed to accurately predict the flow stress. The predicted results demonstrate that the flow stress decreases with the increase of temperature while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The lowered strain rate rapidly decreases the increasing rate of dislocations density in stage II. So the flow stress decreases at the beginning of stage II [39]. On the contrary, when the strain rate is suddenly increased, the opposite results are obtained.…”
Section: Flow Characteristics Deformation Mechanismsmentioning
confidence: 86%
“…The lowered strain rate rapidly decreases the increasing rate of dislocations density in stage II. So the flow stress decreases at the beginning of stage II [39]. On the contrary, when the strain rate is suddenly increased, the opposite results are obtained.…”
Section: Flow Characteristics Deformation Mechanismsmentioning
confidence: 86%
“…Compared with the extrusion process, it significantly simplified the process and improved the production efficiency [13]. Dai et al [14] found that dynamic recrystallization and dynamic transformation were the dominant restoration mechanisms during the hot deformation process. Zhang et al [15] applied the spinning ultrasonic-surface-rolling process (S-USRP) to manufacture thin-walled pure titanium tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Fe has been a popular element used in recent years to design new low elastic modulus and high strength titanium alloys due to its strong β phase stabilization and low cost. Our latest work [4][5][6] reveals that Ti-Fe binary alloys with trace Fe addition (Fe < 4 wt.%) are presenting an excellent mechanical property, better corrosion resistance and good biocompatibility when compared with pure titanium and most Ti-X binary alloys designed for dental implants application due to the phase composition controlling and grain refinement effects. By adding 3 wt.% Fe in Ti-25Nb alloy, Lee et al [7] found that the bending strength/modulus ratio of the Ti-25Nb-3Fe is enhanced about 41.4% when compared to that of Ti-6Al-4V.…”
Section: Introductionmentioning
confidence: 99%